(untitled) (Archaeologia Adriatica, 2017)
Underwater reconnaissance of the maritime zone of the island of Pašman near the island of Babac uncovered archaeological finds from the late medieval and post-medieval period. The finds were discovered in the western cove of the island of Babac facing the settlement of Pašman on the homonymous island. The Pašman Channel is narrowest at this spot, and the site was probably used as an anchorage owing to favourable natural position and because it was a good shelter from all winds. Recovered material was found at the depth of 3 to 4 meters. Pottery represents most abundant category of finds with dominant glazed kitchenware and tableware while glass vessels are represented by a small number of specimens. Typologically diverse finds indicate that the site was probably used as an anchorage for centuries where ships sought shelter in bad weather or spent night.